Development of Noncovalent Supported Ionic Liquid Phase Catalyst (SILPC) for Liquid-Phase Reaction as a Benign and Sustainable Protocol to Immobilize Homogeneous Catalyst - Hagiwara, Hisahiro (Synlett, 2012)
Homogeneous catalysts were immobilized to the pores of amorphous inorganic supports with the aid of an ionic liquid as Pd-, Cu-, and Ru-supported ionic liquid phase catalyst (SILPC), which is a benign method to immobilize sophisticated but unstable homogeneous catalysts so far difficult to load in an inorganic support by simple impregnation method. By immobilizing as a SILPC, sustainability and reactivity of catalysts increased in Mizoroki–Heck reaction, Suzuki–Miyaura reaction, Huisgen [3+2] cycloaddition (click reaction) without external ligand in aqueous media and ambient atmosphere, and olefin metathesis reactions. In addition, palladium was immobilized on nano-silica gel dendrimer as a nano-SILPC, which was highly active to Suzuki–Miyaura reaction. Moreover, MacMillan imidazolidinone organomolecular catalyst was immobilized as a Mac-SILPC to enable sustainable asymmetric Diels–Alder reaction. SILPCs could be repeatedly used by filtration.1 Introduction2 Recyclable Mizoroki–Heck Reaction in an Ionic Liquid Catalyzed by Pd/C3 Immobilization of Pd in an Amorphous Inorganic Oxide with the Aid of an Ionic Liquid – Preparation of Pd-SILPC4 Mizoroki–Heck Reaction Catalyzed by Pd-SILPC5 Mizoroki–Heck Reaction in Water Catalyzed by Pd-SILPC6 Suzuki–Miyaura Reaction Catalyzed by Pd-SILPC7 Immobilization of Pd in Nano-Silica Gel Dendrimer as Pd-Nano-SILPC and Suzuki–Miyaura Reaction8 Polymer-Coated Pd-SILPC and Suzuki–Miyaura Reaction9 Catalytic Hydrogenation Catalyzed by Pd-SH-SILPC10 Immobilization of Cu as Cu-SILPC and Huisgen [3+2] Cycloaddition11 Immobilization of Grubbs Catalyst as Ru-SILPC and Olefin Metathesis Reaction12 Immobilization of MacMillan Organocatalyst as Mac-SILPC and Asymmetric Diels–Alder Reaction13 Conclusions
Keywords: ionic liquids; heterogeneous catalysis; catalyst immobilization; SILPC; supported catalysis